Unexpected Political News And Its Impact On Stock Returns: Evidence From Karachi Stock Exchange - Quratul ain Hafeez, Chowdhery (2010)
The study examines the effect of unexpected, surprise political events on stocks in the Karachi stock exchange. The study used daily closing prices on a sample portfolio of the 50 most performing stocks on the exchange, ranging over a time span of almost 26 months from August of 2006 till the August of 2008. In the empirical analysis, the non regressive event study methodology was used to calculate abnormal returns on the stocks by using the returns on the market index as a proxy, followed by a paired t-statistic to test for significant changes in stock returns. The results indicated that two out of the eight events under consideration resulted in significantly abnormal returns for the sample portfolio. In all the 8 events a few stocks always presented with significantly abnormal returns as a result of the event but on an individual basis. It was also observed that the market was extremely volatile and following every event was able to dilute the effect of it soon enough. The stock market has been so used to constant changes in the political condition of the country that most stocks were unable to mirror the effect of the incident in their returns.